Efficacy of fire needle on patients of facial spasm: A protocol for systematic review and meta analysis. Issue 43 (23rd October 2020) - Zhong, Zhiying; Xiong, Jun; Lu, Lunbin; Chen, Jun; Tang, Genhua; Zhu, Siyuan; Zhou, Xingchen; Guo, Han
Abstract: Background: Facial spasm causes a lot of troubles to patients daily life and seriously affects their mental and physical health. Relevant studies have shown that fire needle therapy has certain benefits for facial spasm, is an integral part of acupuncture therapy. However, there is no unanimous conclusion. The main purpose of our study is to measure whether fire needle therapy is effective for facial spasm. Methods: The following electronic databases will be searched for the collection of fire-needle related randomized controlled trials (RCTS) for facial spasm, including 4 English databases (Web of Science, the Cochrane Library, EMBASE, Pubmed) and 3 Chinese databases (Chinese National Knowledge Infrastructure [CNKI], Wanfang data, Chinese VIP Information). The cure rate and total effective rate are the main outcomes, while the intensity, frequency, recurrence rate and adverse events are the secondary outcomes. We will use Endnote software X9 for study selection, Review Manager software 5.4 and STATA 13.0 software for analysis and synthesis. Results: We will evaluate the efficacy of fire needles in the treatment of facial spasm in combination with current studies. Conclusion: The conclusion of this study will provide evidence for the efficacy of fire needle in the treatment of facial spasm. Trial registration number: INPLASY202080036.